Direct observation of dislocation formation and plastic anisotropy in Nb2AlC MAX phase using in situ nanomechanics in transmission electron microscopy - Kabiri, Yoones; Schrenker, Nadine; Müller, Julian; Mackovic, Mirza; Spiecker, Erdmann (Scripta Materialia, 2017)
We report on the direct observation of nucleation and propagation of basal plane dislocations in Nb2AlC, a member of MAX phases, using nanomechanical testing inside a transmission electron microscope. Different loading directions with respect to the basal plane resulted in completely different plastic response due to the pronounced anisotropy of the layered crystal. Discrete dislocation activities were correlated to distinct events in the force-displacement curves. In situ observations together with post-mortem contrast analyses of deformed regions show no indication of cross-slip or entanglement of dislocations during the indentations.
Keywords: Transmission electron microscopy (TEM); Nanoindentation; Dislocation nucleation; Mechanical properties; MAX phases